(untitled) (BIRDEM Medical Journal, 2020)
Background: Coronavirus disease 2019 (COVID-19) is a potentially fatal disease with multisystem involvement. Several studies have reported various electrolyte abnormalities at admission in patients who progress to the severe form of COVID-19. This study evaluated the electrolyte pattern in confirmed and critically ill COVID-19 patients. Methods: This cross sectional study was carried out in the department of critical care medicine of BIRDEM General Hospital, Dhaka, Bangladesh, from 1st July to 10th November, 2020. Total 70 RT-PCR positive, critically ill COVID-19 patients, were enrolled. Patients’ demographic profile, clinical features, admission electrolyte report, length of ICU stay and outcome were documented in case record forms. Results: In this cohort, total 70 RT-PCR positive COVID-19 cases (male 41, female 29, mean age 62.9 ± 13.3years) were enrolled. Fifty eight (82.85%) patients had different electrolytes abnormalities including hyponatraemia (54, 77.1%), hypokalaemia (35, 50%), hypocalcaemia (20, 28.6%) and hypomagnesaemia (11,15.7%). Regarding clinical symptoms, 98.6% (n=69) had respiratory distress, 97.1% (n=68) had cough, 94.3% (n= 66) had history of fever and 10.0 % (n=7) presented with unconsciousness. Diabetes mellitus (DM) was the most common co morbidity (94.3%).Mean length of ICU stay were 6.4 ± 3.4 days, where 48.57% (n=34) survived and 51.42% (n=36) died. Among 36 death cases, 33 patient (91.7%) had hyponatraemia (p value=0.003), which was statistically significant. Conclusion: In this study, we found that, hyponatraemia was the most predominant electrolyte abnormality. Among 36 death cases, around 92% had hyponatraemia. Like other studies, it showed that various electrolyte imbalances seem to have an impact on disease process. So, base line electrolyte assessment would be beneficial for evaluating the risk of severity of COVID-19. So, more study of electrolytes in COVID-19 cases with multi center approach is needed. Birdem Med J 2020; 10, COVID Supplement: 46-50